L’utilité du Moyen Âge - Jeff Rider (Itinéraires)
The Middle Ages are, today, a body of artifacts produced during a certain time in a certain region that still survives and, more importantly, the worlds we imagine on the basis of these artifacts. Imagining these past worlds, whether from a historicist, academic point of view or from an anachronistic, popular point of view is useful to us because it helps us discover new modes of being-in-the-world, new capacities for knowing ourselves, and improve our abilities to understand and to configure the experiential world and our lives.